Advanced Extramammary Paget's Disease of the Groin, Penis, and Scrotum. (January 2014) - Isrow, Derek; Oregel, Karlos Z.; Cortes, Javier; Gomez, Henry; Milikowski, Clara; Feun, Lynn; Silva, Orlando
Extramammary Paget's disease (EMPD) is a rare intraepithelial malignancy arising in areas rich in apocrine glands, such as the perineum, vulva, axilla, scrotum, and penis. We describe the case of a man in his 50s who initially presented with a small eczematous lesion on his right groin, treated with topical ointments for eczema, until excisional biopsy of lesion unequivocally revealed invasive EMPD. Despite aggressive surgical interventions, his disease progressed to involve the scrotum and penis. Deemed unresectable, the patient was treated with systemic chemotherapy with minimal response. The rarity of EMPD, especially of the penis and scrotum, warrants an educated eye and heightened index of suspicion when dealing with eczematous lesions in the groin in any person. Early biopsy and histological examination is crucial for early surgical intervention of the lesions. There are no guidelines available to treat locally advanced unresectable disease. In addition, further studies are needed to identify genetic defects underlying the pathogenesis of this rare disease, to help improve treatment strategies and decrease morbidity.